Measurement of radon activity concentration in elementary schools in Tuzla, Bosnia and Herzegovina - Kasić Amela; Kasumović Amira; Hodžić Muhamed (Nuclear Technology and Radiation Protection)
In this paper, the results of measurements of indoor radon activity concentration in fourteen elementary schools in Tuzla, Bosnia and Herzegovina, are presented. Measurements were performed with CR-39 solid-state nuclear track detectors. Radon activity concentration in investigated locations was 6.8-143 Bqm-3. To assess the indoor radon hazards for people, the annual effective dose, excess lifetime cancer risk, and the relative risk of lung cancer were estimated.